Cooperative Polar/Steric Strategy in Achieving Site‐Selective Photocatalyzed C(sp3)−H Functionalization. Issue 36 (9th June 2017) - Yamada, Keiichi; Fukuyama, Takahide; Fujii, Saki; Ravelli, Davide; Fagnoni, Maurizio; Ryu, Ilhyong
Abstract: Synergistic control over the SH 2 transition states of hydrogen abstraction exploiting polar and steric effects provides a promising cooperative strategy for site‐selective C(sp 3 )−H functionalization using decatungstate anion photocatalysis. By using this photocatalytic approach, the C−H bonds of substituted lactones and cyclic ketones were functionalized selectively. In the remarkable case of 2‐isoamyl 4‐tert‐butyl cyclohexanone (1 t ) bearing five methyl, five methylene, and three methine C−H bonds, one methine C−H bond in the isoamyl tether was selectively functionalized. Abstract : Synergistic control over the SH 2 transition states of hydrogen abstraction by polar and steric effects provides promising insight into site‐selective C(sp 3 )−H functionalization using decatungstate anion ([W10 O32 ] 4− ) photocatalyt. Even with many possible C−H reaction sites, transformation only occurs at the positions marked in blue for the given molecules.